2020
DOI: 10.3390/molecules25122856
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a New Barbituric Acid Derivative Exerts Antiproliferative and Antimigratory Effects against Sorafenib Resistance in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common cause of cancer death worldwide. Sorafenib, a multikinase inhibitor, is the first-line drug approved by the Food and Drug Administration (FDA) for the treatment of patients with advanced HCC. However, most patients who continuously receive sorafenib may acquire resistance to this drug. Therefore, it is important to develop a new compound to treat liver cancer and sorafenib-resistant liver cancer. Barbituric acid derivatives have been used as antiasthmatic drugs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…6d, Supplementary Figure S5e, f). Mounting data demonstrate that AKT-mTOR and their downstream target molecules such as elF4EBP1 and p70S6K act as positive regulators for HCC progression [18][19][20][21]. In compatible with this, we herein found that LINC00680 knockdown significantly suppressed the phosphorylation of mTOR, elF4EBP1, and p70S6K, whereas overexpression of LINC00680 enhanced their phosphorylation (Fig.…”
Section: Mir-568 Targets To Akt3 In Hccsupporting
confidence: 83%
“…6d, Supplementary Figure S5e, f). Mounting data demonstrate that AKT-mTOR and their downstream target molecules such as elF4EBP1 and p70S6K act as positive regulators for HCC progression [18][19][20][21]. In compatible with this, we herein found that LINC00680 knockdown significantly suppressed the phosphorylation of mTOR, elF4EBP1, and p70S6K, whereas overexpression of LINC00680 enhanced their phosphorylation (Fig.…”
Section: Mir-568 Targets To Akt3 In Hccsupporting
confidence: 83%
“…To show the utility of the method and to investigate their efficiencies towards Mtu Ung, different uracil derivatives were screened to bind to Mtu Ung in terms of thermodynamic parameters [ 33 ] and computational analysis with measure of docking score using Schrödinger Software ( Table 1 ). In addition, barbituric acid was checked owing to its high similarity to the uracil ring and its general applicability in inhibitor design for a variety of targets [ [50] , [51] , [52] , [53] ]. The selected compounds were analysed for dose dependent inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting data demonstrate that AKT-mTOR and their downstream target molecules such as elF4EBP1 and p70S6K act as positive regulators for HCC progression [18][19][20][21]. In compatible with this, we herein found that LINC00680 knockdown signi cantly suppressed the phosphorylation of mTOR, elF4EBP1, and p70S6K, whereas overexpression of LINC00680 enhanced their phosphorylation (Fig.6e).Taken together, these results suggested that miR-568/AKT3/mTOR signaling axis mediated the oncogenic effects of LINC00680 in HCC.…”
Section: Linc00680 Sponges and Down-regulates Mir-568 Level In Hcc VImentioning
confidence: 99%